A Study on the Properties of Foams Produced with Cellulose-Based Molecules with an Outlook on Flotation - Ted Nuorivaara; Rodrigo Serna-Guerrero (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
"As the demand of raw materials increases in a global scale due to demographic and economical changes, it is necessary to find technological solutions that improve current production processes in an efficient and sustainable manner. The main objective of this preliminary study is to evaluate the properties of foam produced with a cellulose-based molecule as an alterative to commercial frothing agents in flotation operations. There are two potential advantages identified with the use of cellulose-based additives for the proposed application: i) these chemicals can be produced from sustainable sources (i.e., non-edible crops), and ii) cellulose can be functionalized with chemical groups, in order to rationally modify its behaviour. In previous studies dealing with foam stabilization, it has been proposed that some functionalized cellulose species present a self-assembly mechanism at gas-liquid interfaces. Unlike typical surfactant-based frothers, cellulose molecules form networks around the bubbles that act as protective layers to the mechanical stress and to the occurrence of ionic species. This work studied the properties of foams produced in the presence of a partially hydroxylated cellulose molecule (i.e., hydroxypropyl methyl cellulose; HPMC) under various concentrations in a laboratory-scale column. A comparison with a commercial surfactant frother (i.e., Nasfroth 240) is presented, and a rationalization of the behaviour of HPMC in terms of foam properties (i.e., surface tension, bubble size, foam depth) is proposed. INTRODUCTIONThe search for green alternatives to chemicals produced from non-renewable sources has become a topic of major relevance in industry (Choi et al., 2015). As a chemical consuming industry, the mining sector faces now the challenge of adopting new processing technologies and strategies in order to achieve the future demands of sustainability. Evidently, a move towards green chemistry can only take place by identifying substitute molecules offering potential advantages in terms of recovery and grade."